Biomass energy consumption and sustainable human development: the role of financial development in EAC member countries - Ali Yassin Sheikh Ali; Ali Abdukadir Ali Gutale; Mohamed Saney Dalmar (Cogent Economics & Finance, 2024)
Researchers are still in conflict on how biomass energy usage affects the environment, the economy, and human development. Moreover, since its inception, climate change has become one of humanity's greatest challenges, inspiring massive efforts to lessen its effects and concentrate on sustainable development. This study examined the relationship between biomass energy consumption and sustainable human development in East African Community (EAC) member states between 1990 and 2019. This study uses econometric approaches to address the challenges of cross-sectional dependence and slope heterogeneity. We used the CIPS and CADF unit root tests together with the Westerlund cointegration test to address these issues. Additionally, Contemporaneous Correlation estimators (Feasible Generalized Least Squares - FGLS) and Panel Corrected Standard Errors - PCSE) and the Fully Modified Ordinary Least Squares (FMOLS) were employed. We also used the Dumitrescu-Hurlin panel causality test. Our analysis revealed that the East African Community (EAC) members' sustainable human development (SHD) is threatened by biomass energy consumption (BEC), which has a coefficient of -0.920. The BEC-SHD nexus is found to be reversed by the moderating impact of financial development, with an interaction coefficient of 0.329. Finally, we successfully demonstrated the existence of a bidirectional causal relationship between BEC and SHD as well as BEC and EG. This study provides a thorough analysis of the complex connection between the use of biomass energy and the promotion of sustainable human development in the member states of the East African Community (EAC) during a span of 30 years (1990-2019). By employing sophisticated econometric techniques to tackle issues of cross-sectional dependence and slope heterogeneity, our research reveals a substantial adverse effect of biomass energy use on sustainable human development, as shown by a coefficient of -0.920. Significantly, the study demonstrates that financial development might alleviate this negative impact, indicating that measures targeted at improving financial infrastructure should encourage more sustainable utilization of biomass energy. The bidirectional causal linkages between biomass energy consumption, sustainable human development, and economic progress have been shown, highlighting the intricate nature of energy policy in the region. These insights are crucial for policymakers as they offer empirical information to inform the creation of strategies that effectively balance energy requirements with sustainable development goals. This ultimately promotes a more resilient and fair future for the East African Community (EAC).
Keywords: 330; Biomass energy consumption; sustainablehuman development; East African Community; Climate change; Financial Development